Can Ntfps Help Eradicate Poverty? A Case Study from Tropical Lowland Rainforest of Southwest Nigeria (2011)
The study investigated the potential of NTFP trade towards eradicating poverty, by analyzing revenues accruable to harvesters and marketers of five top priority NTFP species including: bush mango (Irvingia gabonensis), African walnut (Tetracarpidiwn conophorum syn. Plukenetia conophora), chew-stick (Massularia acuminata), fever bark (Anninckia chloranta syn. Enantia chloranta) and bush pepper (Piper guineense) in the tropical lowland rainforest of Omo and Shasha Forest Reserves, Southwest Nigeria. The snowball method as well as a simple random sampling technique was used to select harvesters and marketers for questionnaire surveys. Information were gathered on products harvesting and utilization patterns, units of marketing of the products and pricing, influence of seasonality on product availability, and average quantity of products harvested and sold in a month among others. The data generated from the survey were subjected to descriptive statistics. The statistical model for student’s t-test was used to compare the contributions of NTFPs and other source(s) of income of respondents. Results revealed a significant difference between the income generated from the selected products and those from other sources. All the NTFPs except Irvingia gabonensis currently have low- medium likelihood of helping to eradicate poverty. There is a marked influence of seasonality on the potentials of the selected species in income generating activities. There is also a wide reflection of decreasing trend in the availability of selected NTFPs, particularly among harvesters, thus portending an ominous picture of the resource base. Our results suggest that the potential of NTFPs towards helping in the eradication of poverty remains conjectural. There is therefore, the need for a conscious and concerted effort towards the improvement of the NTFP sector for both conservation and economic development.